The Experimental Study on Chaenomelis Fructus(木瓜) in Case of the Arthritis Induced by Injecting Freund's Complete Adjuvant - Kwon, Kang; Park, Ki-Chul; Sohn, Seong-Hyun; Park, Hee-Soo (Korean Pharmacopuncture Institute, 2003)
Objective : We carried out this experimental study in order to investigate the effect of Chaenomelis Fructus(목과(木瓜)) extract and herbal-acupuncture on the arthritis induced by injecting Freund's complete adjuvant. Methods : 1.We categorized SD-rats into five groups as followings. ① Control: Without any Treat ② Treat I: treated by acupuncture ③ Treat II: treated by drinking 5% saline ④ Treat III: treatedbydrinking Chaenomelis Fructus(木瓜)) extract ⑤ Treat IV: treated by Chaenomelis Fructus(木瓜) herbal-acupuncture 2. We established ten items for decision of experimental results as followings Edema rate, Pain endurance, WBC, Hemoglobin, Platelet, Total protein, Albumin, Globulin, RA factor, CRP Results : The groups that showed significant effects compared with Contol group were explained as followings. 1. Edema rate: Treat I, Treat III 2.Pain endurance: Treat I, Treat IV 3.WBC: Treat IV 4.Hemoglobin: Treat III 5.Platelet: Treat IV 6.Total protein: Treat I, Treat IV 7.Albumin: None 8.Globulin: Treat I, Treat IV 9. RA factor: Treat I, Treat IV 10.CRP: Treat IV Conclusion : Observing above experimental results, we can guess that the effects of acupuncture and Chaenomelis Fructus(木瓜) herbal-acupuncture on Freund's adjuvant arthritis are more superior than other ways. In addition, we can find that the latter is more better than the former in effect by two items(platelet, CRP)